“Youth is Drunke with Pleasure, and therefore Dead to all Goodnesse”: Regulating the Excess of the Erotic Early Modern Body - Orman, Steve (Text Matters: A Journal of Literature, Theory and Culture, 2013)
This article investigates the erotic and youthful body in John Fletcher’s play The Faithful Shepherdess, written for The Children of the Queen’s Revels c.1607. For many early modern scholastic, medical, and conduct manual writers, the life stage of Youth was a particularly dangerous moment in an individuals’ life, a time where the body was in a constant state of flux and ruled by unhealthy bodily excess. Fletcher’s play presents an assortment of characters who are all ruled by or obsessed with their own youthful passions. This article engages with Galenic humoral theory, an area that has been neglected in scholarship on Fletcher’s play, to provide a close analysis of Youth and erotic excess on the early modern stage.